Prevalence of gastrointestinal pathogens in Sub-Saharan Africa: systematic review and meta-analysis - Stephanie M. Fletcher; Damien Stark; John Ellis (AOSIS, 2011)
A significant proportion of vulnerable people in sub-Saharan Africa (SSA) remain at risk for contracting diarrhoeal diseases due to the presence of many risk factors facilitating their transmission. A systematic review of published articles from the SSA region was done to determine the prevalence and types of diarrhoeal pathogens in circulation, based on a search of databases, including EBSCO host, PubMed, Scopus, Science Direct, Google scholar and Web of Science was done between September 2009 and December 2010. Data were summarized from 27 studies, with pooled data analysed and reported. Pathogens were isolated from between 26.8-65.6% of cases, with an overall isolation rate of 55.7% (95% CI, 48.2-62.9%). Isolation rates were highest amongst adult cases followed by children, and the odds of isolating a pathogen was greater in diarrhoeal cases (Odds Ratio 4.93 (95% CI, 1.99 to 12.23), than in asymptomatic controls. Overall isolation ranged from 8% to 99%; and heterogeneity testing suggests differences between age groups (Q=5.806; df=2, P=0. 055). Mixed E. coli spp., (29.95%), Cryptosporidium (21.52%), Cyclospora (18%), Entamoeba, (13.8%), Shigella spp. (10.49%), Salmonella spp. (8.36%), and Campylobacter spp. (8.33%), were most commonly reported, and rotavirus was the most common virus isolated. This is the first review to look at the range of enteric pathogens circulating in SSA, and has confirmed high rates of isolation of pathogens from diarrhoeal cases. Public health practitioners can use this information to understanding the challenges related to diarrhoeal illness and set priorities for their prevention and control.